Soil microbial and plant biomass carbon allocation within perennial and annual grain cropping systems - Galen Bergquist; Craig Sheaffer; Manbir Rakkar; Don Wyse; Jacob Jungers; Jessica Gutknecht (Agriculture, Ecosystems & Environment, 2025)

Soil health improvements from using a novel perennial grain during the transition to organic production - Manbir Rakkar; Jacob M. Jungers; Craig Sheaffer; Galen Bergquist; Julie Grossman; Fucui Li; Jessica LM Gutknecht (Agriculture, Ecosystems & Environment, 2023)

Biomass Production of Prairie Cordgrass (Spartina pectinata Link.) Using Urea and Kura Clover (Trifolium ambiguum Bieb.) as a Source of Nitrogen - SungUn Kim; Kenneth Albrecht; Craig Sheaffer; Dokyoung Lee; Senthil Subramanian; Vance Owens (BioEnergy Research, 2020)
Optimizing nitrogen (N) management is an important factor for sustainable perennial biomass systems. However, N application is costly, both financially and environmentally. Our objectives were to determine: (1) N rate and plant spacing effects on yield and yield components of prairie cordgrass swards and (2) fertilizer N replacement value (FNRV) of kura clover in prairie cordgrass-kura clover binary mixtures. Plots were established in Illinois, Minnesota, South Dakota, and Wisconsin, USA, in 2010. Kura clover was transplanted on 30-cm centers in all treatments in which it was a component; prairie cordgrass seedlings were transplanted within the kura clover on 60- and 90-cm centers. Monoculture prairie cordgrass stands were established at the same population densities of mixed stands and fertilized with 0, 75, 150, or 225 kg N ha -1 . Biomass was harvested in the autumn from 2011 to 2013. N (urea), year, plant spacing, and year × plant spacing affected prairie cordgrass production at all locations. Prairie cordgrass yield increased with N application, but the response varied by location. N application tended to increase prairie cordgrass tiller density and consistently increased tiller mass. Prairie cordgrass yield with 0 N was equal to or less than the yield of prairie cordgrass/kura clover mixtures at all locations in 2011 and 2012; however, kura clover provided a FNRV of 25–82 kg N ha -1 to prairie cordgrass in 2013. Kura clover has potential to provide N to prairie cordgrass in binary mixtures of these two species and on land that may not be easily farmed due to wetness.

Biophysical interactions in perennial biomass alley cropping systems - Joshua D. Gamble; Gregg Johnson; Dean A. Current; Donald L. Wyse; Diomides Zamora; Craig C. Sheaffer (Agroforestry Systems, 2019)

Competition between introduced Bradyrhizobium japonicum strains and indigenous bradyrhizobia in Minnesota organic farming systems - Reda A. I. Abou-Shanab; Manoosak Wongphatcharachai; Craig C. Sheaffer; James C. Orf; Michael J. Sadowsky (Symbiosis, 2017)

Maize Stover and Cob Cell Wall Composition and Ethanol Potential as Affected by Nitrogen Fertilization - Aaron J. Sindelar; Craig C. Sheaffer; John A. Lamb; Hans-Joachim G. Jung; Carl J. Rosen (BioEnergy Research, 2015)

Nitrogen and Tillage Management Affect Corn Cellulosic Yield, Composition, and Ethanol Potential - Aaron J. Sindelar; John A. Lamb; Jeffrey A. Coulter; Craig C. Sheaffer; Jeffrey A. Vetsch (BioEnergy Research, 2015)

Harvest Date Effects on Biomass Yield, Moisture Content, Mineral Concentration, and Mineral Export in Switchgrass and Native Polycultures Managed for Bioenergy - Joshua D. Gamble; Jacob M. Jungers; Donald L. Wyse; Gregg A. Johnson; John A. Lamb; Craig C. Sheaffer (BioEnergy Research, 2015)

The Effect of Nitrogen, Phosphorus, and Potassium Fertilizers on Prairie Biomass Yield, Ethanol Yield, and Nutrient Harvest - Jacob M. Jungers; Craig C. Sheaffer; John A. Lamb (BioEnergy Research, 2015)

Establishing Native Perennial Bioenergy Crops with Cereal Grain Companion Crops - Jacob M. Jungers; Donald L. Wyse; Craig C. Sheaffer (BioEnergy Research, 2015)

Soil Streptomyces communities in a prairie establishment reflect interactions between soil edaphic characteristics and plant host - Laura Felice; Nicholas R. Jordan; Ruth Dill-Macky; Craig C. Sheaffer; Laura Aldrich-Wolfe; Sheri C. Huerd; Linda L. Kinkel (Plant and Soil, 2015)

Establishment and early productivity of perennial biomass alley cropping systems in Minnesota, USA - Joshua D. Gamble; Gregg Johnson; Craig C. Sheaffer; Dean A. Current; Donald L. Wyse (Agroforestry Systems, 2014)

Biomass production potential of grasslands in the oak savanna region of Minnesota, USA - Peter A. Gillitzer; Donald L. Wyse; Craig C. Sheaffer; Steven J. Taff; Clarence C. Lehman (BioEnergy Research, 2013)

Variation due to Growth Environment in Alfalfa Yield, Cellulosic Ethanol Traits, and Paper Pulp Characteristics - Katie Petersen Rock; Ryan T. Thelemann; Hans-Joachim G. Jung; Ulrike W. Tschirner; Craig C. Sheaffer; Gregg A. Johnson (BioEnergy Research, 2009)